2011
DOI: 10.1002/nbm.1640
|View full text |Cite
|
Sign up to set email alerts
|

Substrate selection in hearts subjected to ischemia/reperfusion: role of cardioplegic solutions and gender

Abstract: In conditions of ischemia/reperfusion (I/R), the relative use of all available substrates by the heart has a significant effect on the recovery of the organ. This substrate preference in perfused hearts is influenced by ischemia. We followed the metabolic fate of [U-(13) C]glucose and [3-(13) C]lactate in hearts preserved in Celsior (Cs) and histidine buffer solution (HBS) for 4 or 6 h and subsequently perfused with a Krebs-Henseleit solution (KH) containing [U-(13) C]glucose and [3-(13) C]lactate. We also ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…The ability to administer β-estradiol or any medication to reduce renal IRI in a transplantation setting depends on the persistence of its beneficial effects or, at a minimum, the lack of detrimental effects in the procurement of other organs. Sex differences in IRI tolerance are well described in cardiac tissue (7,31,32) and the nervous system (8,33), and short-term administration of 17β-estradiol directly improved IRI tolerance in rat livers (9) and myocardium (34) when given 1 and 3 hours before injury, respectively, making nonrenal off-target effects of lesser concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to administer β-estradiol or any medication to reduce renal IRI in a transplantation setting depends on the persistence of its beneficial effects or, at a minimum, the lack of detrimental effects in the procurement of other organs. Sex differences in IRI tolerance are well described in cardiac tissue (7,31,32) and the nervous system (8,33), and short-term administration of 17β-estradiol directly improved IRI tolerance in rat livers (9) and myocardium (34) when given 1 and 3 hours before injury, respectively, making nonrenal off-target effects of lesser concern.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dimorphism with respect to tolerance of IRI has been noted in a number of laboratory animal models (7)(8)(9)(10)(11). Generally, there is consensus that female sex conveys greater tolerance of, or protection from, IRI relative to the male sex.…”
Section: Introductionmentioning
confidence: 99%
“…Proton nuclear magnetic resonance ( 1 H NMR) 1 H NMR spectra were acquired as previously described [30]. Sodium fumarate (final concentration of 1 mM) was used as an internal reference (6.50 ppm) to quantify the following metabolites present in the extracellular media of hSCs (multiplet, ppm): lactate (doublet, 1.33); alanine (doublet, 1.45), acetate (singlet, 1.90), pyruvate (singlet, 2.35), citrate (multiplet, 2.57-2.72) and H1-a-glucose (doublet, 5.22).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…To satisfy its high-energy requirements, the cardiac muscle is capable of consuming several substrates, but glucose plays a key role, particularly when the heart is subjected to unfavourable conditions (Alves, Oliveira, & Carvalho, 2011). Among the several metabolic alterations induced by hyperglycaemia, it has been reported that the myocardium accelerates glycolysis, producing high levels of lactate, and this may be a contributing factor for the cardiac dysfunction associated with DM.…”
Section: Introductionmentioning
confidence: 99%